Supression of a monastery: Canon 616 §4 (Roman replies and CLSA advisory opinions ; 2010, 2010)
During the past two or three years, there have been monasteries of nuns suppressed in the United States due to the aging communities and the lack of vocations. The Congregation for Institutes of Consecrated Life and Societies of Apostolic Life sends an executorial decree of suppression in response to the nuns' petition or the bishop's recommendation to the Congregation. The latter exercises vigilance over the monastery and must consider the welfare of the aging nuns (canon 615).